Arabidopsis Class I α-Mannosidases MNS4 and MNS5 Are Involved in Endoplasmic Reticulum–Associated Degradation of Misfolded Glycoproteins . Issue 4 (15th April 2014) - Hüttner, Silvia; Veit, Christiane; Vavra, Ulrike; Schoberer, Jennifer; Liebminger, Eva; Maresch, Daniel; Grass, Josephine; Altmann, Friedrich; Mach, Lukas; Strasser, Richard
Abstract : Protein quality control mechanisms in the endoplasmic reticulum ensure that only correctly folded proteins are delivered to other compartments of the secretory pathwa, while misfolded proteins are degraded. This study identified and characterized the mannosidases that generate the glycan structure acting as the degradation signal for misfolded glycoproteins in Arabidopsis . Abstract: To ensure that aberrantly folded proteins are cleared from the endoplasmic reticulum (ER ), all eukaryotic cells possess a mechanism known as endoplasmic reticulum–associated degradation (ERAD ). Many secretory proteins are N -glycosylated, and despite some recent progress, little is known about the mechanism that selects misfolded glycoproteins for degradation in plants. Here, we investigated the role of Arabidopsis thaliana class I α-mannosidases (MNS1 to MNS5) in glycan-dependent ERAD . Our genetic and biochemical data show that the two ER -resident proteins MNS4 and MNS5 are involved in the degradation of misfolded variants of the heavily glycosylated brassinosteroid receptor, BRASSINOSTEROID INSENSITIVE1, while MNS1 to MNS3 appear dispensable for this ERAD process. By contrast, N -glycan analysis of different mns mutant combinations revealed that MNS4 and MNS5 are not involved in regular N -glycan processing of properly folded secretory glycoproteins. Overexpression of MNS4 or MNS5 together with ER -retained glycoproteins indicates further that both enzymes can convert Glc0-1 Man8-9 GlcNAc2 into N -glycans with a terminal α1, 6-linked Man residue in the C-branch. Thus, MNS4 and MNS5 function in the formation of unique N -glycan structures that are specifically recognized by other components of the ERAD machinery, which ultimately results in the disposal of misfolded glycoproteins.